Mid-term durability of polytetrafluoroethylene patches in unicuspid aortic valve repair. (31st August 2020) - Karliova, Irem; Ehrlich, Tristan; Matsushima, Shunsuke; Ewen, Sebastian; Schäfers, Hans-Joachim
Abstract: OBJECTIVES: Unicuspid aortic valve (UAV) morphology is a cause for aortic valve dysfunction in childhood or adolescence. Repair requires the use of patch material, and polytetrafluoroethylene (PTFE) has been proposed for this purpose because of lack of calcification. We reviewed our mid-term experience with PTFE for the repair of UAV to analyse the durability of this technique. METHODS: Out of 21 patients with an UAV undergoing aortic valve repair for severe aortic regurgitation between 2014 and 2016, 11 patients (52%) were treated using PTFE patch material. Aortic regurgitation was present in all patients, the primary indication for surgery was regurgitation in 8, stenosis in 2 and aneurysm in 1. Symmetric bicuspidization of the UAV was performed in all. One patient required additional root remodelling for root dilatation, and another 3 tubular ascending aortic replacement. RESULTS: No patient died in hospital or during follow-up. Seven patients (63.6%) required reoperation for progressive AR. Freedom from reoperation was 58% at 1 and 35% at 5 years postoperatively. At reoperation the PTFE patches were found dehisced from aortic wall and/or native cusp tissue. In 3 patients re-repair was performed; a stable result was achieved in 1. Two patients underwent valve replacement 3 months and 1 year postoperatively. The other 4 patients underwent valve replacement. CONCLUSIONS: The repair of UAVs using PTFE patch is associated with poor durability, a more durable patch with better healing characteristics material is needed. Abstract : The unicuspid aortic valve (UAV) is a rare congenital morphology that often requires aortic valve surgery in childhood and young adulthood.